Implementación de un prototipo de tricimoto para personas con paraplejía - Guanga Balseca, Ronnie Santiago (2017)
People with paraplegia face daily urban walls, due to the lack of an economic means of transportation and adequate to their abilities, it interferes with the individual's ability to be independent and their performance in society. Considering that people with this disability cannot get rid of their wheelchair, the current project presents the design and construction of a prototype Tricycle-moto by adapting a motorcycle, which will provide independence for people suffering from paraplegia, in this way a solution is provided to their mobility problems so it’s possible to integrate them to a socio-economic environment. The prototype structural system was designed and modeled with projection to optimize resources and materials, but without altering the quality of the same. Tricycle-moto was constructed with materials of approved characteristics by the norms of Ecuadorian regularization, fulfilling quality controls in each stage of construction to provide security and quality to the prototype. Its engine of 150 c.c. provides a power of 10 hp in addition to being economical has a yield of 10 km / l of fuel, the Tricycle-moto will be able to make daily trips to the person different social activities, with a maximum circulation speed of 50 km / h. in order to grantee the safety by the prototype starts from the design, its center of gravity is distributed in a way that can minimize the effects caused by an accident, in addition to the mandatory elements such as the helmet and safety belt that has as its purpose safeguarding the integrity of the individual by proving to be an efficient and economic vehicle. The Tricycle-moto will solve the displacement and autonomy person problems who has mobility problems in their lower limbs.